Early repolarization pattern: a marker of increased risk in patients with catecholaminergic polymorphic ventricular tachycardia - Tueluemen, Erol; Rudic, Boris; Liebe, Volker; Schimpf, Rainer; Borggrefe, Martin (Europace, 2016)
AbstractAims. The early repolarization pattern (ERP) has been shown to be associated with arrhythmias in patients with short QT syndrome, Brugada syndrome, and
Gesehen am 17.07.2019
Online publish-ahead-of-print 23 December 2015